Identifikasi Nematoda Usus Pada Sayuran Lalapan Yang Dijual Di Pasar Tradisional dan Pasar Modern Di Kota Medan - Rama Syahputra; Ida Fauziah; Abdul Karim; Ferdinand Susilo (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2023)
This study aims to determine whether there is contamination of intestinal Nematode parasites found in fresh vegetables sold in Traditional Markets and Modern Markets in Medan City. This research method uses a descriptive method with a total sampling technique to be studied. Where the data that has been obtained and obtained is described or described as it is without intending to make conclusions that apply to the public or generalizations. Then the data can be made in tabular form in accordance with the Laboratory Standards. The results showed that from examining samples from the Brayan market, Sambu market, MMTC Pancing market, Sukaramai Denai market and Simpang Limun market, it was found that 5 samples of cabbage vegetables were contaminated with eggs and larvae of intestinal Nematode parasites and 5 samples of lettuce were contaminated with eggs and larvae of Nematode parasites. intestines. The types of parasites found were Ascaris lumbricoides eggs and Ancylostoma duodenale and Necator americanus larvae. Meanwhile, the samples from Brastagi Plaza, Carefour, Irian Supermarket, Maju Bersama Supermarket, and Cemara Fruit and Vegetable Market showed that 2 samples of lettuce were contaminated with Ascaris lumbricoides worm eggs, and the samples of cabbage and basil vegetables did not find larvae or basil.